Management of Pain with Morphine in Cancer Patients in a Tertiary Care Centre of Nepal - Mahaseth, Rita Kumari; Pun, Rashmey; Shrestha, Kriti (Nepal Medical College Journal, 2021)
Pain is one of the most afflicting symptoms reported by cancer patients, mainly those with metastatic disease. The prevalence of cancer has increased, with an estimated projection of 17 million new cases in 2020. This means that there will be an increase in individuals with pain caused by the disease and by treatment. Morphine has been used to relieve pain in cancer patients for centuries. WHO, created a global health policy document for management of cancer pain entitled “Cancer Pain Relive,1 in which morphine was central. In a retrospective study of 1229 patients with cancer pain, the author reported that the analgesic ladder was effective in 71%. Many patients do not get adequate pain relief. Rationale of this study was to assess cancer related pain by using visual analogue pain scale and to prescribe optimal dose of morphine through dose titration to relieve pain and to improve quality of life. An interventional hospital-based study was done in fifty-two different types of cancer patients from 1st Jan, 2020 to 31st Dec, 2020 at Department of Oncology, Nepal Medical college and Teaching Hospital (NMCTH), Kathmandu. Among them 31 were male and 21 were female with mean age 63.87 and 58.19 respectively and SD +/- 12.10 in male and 16.07 in female with p value 0.152 significant. These patients were assessed for severity of pain through visual pain analogue. Improvement in daily activities after administration of morphine according to ECOG performance scale was done. Constipation was the most common complication induced by morphine 38.5%, sedation 32.7% and nausea in 25%. By understanding the context and social meaning surrounding the use of morphine to treat cancer pain, health care professionals can begin to anticipate, acknowledge and address some of the barrier to its use, thereby enhancing the pain control.